ANALISA PENGENDALIAN KUALITAS TAHU MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) PADA UKM TAHU HAJI MAMAD - Ryan Fajar Rahmadani (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
UKM Tahu Haji Mamad is an industry that is engaged in making tofu and the main raw material is soybeans.This study aimed at determining the quality control of product, the most common types defect in product, the factors in causing defect in product, the action that should be taken to prevent the defect of product at UKM Tahu Haji Mamad by using Statistical Processing Control. this type of research is descriptive with quantitative approach. Collectingdata using interviews and observations, data analysis techniques using four tools ofquality control, the check sheet, histogram, a causal diagram, and a control chart p. Defective products in the finished product every time it isproduced indicates that the quality control carried out by UKM tofu Haji Mamad is still not optimal.Observations and observations made at the Haji Mamad Tofu Factory for 10 days found manydefective products which every day averaged around 46 tofu products.The results showed there arefive types of damage to the product know, that smell, texture,hard, soft texture, there are dirt, and thewrong cut. The most dominant is the kind ofdamage a hard texture, which is about 41.74% compared to all the damage knew theothers. P control chart analysis results are known there are 6 observations that areoutside the control limit of a total of 10 observations.UKM Tahu Haji Mamad is an industry that is engaged in making tofu and the main raw material is soybeans.This study aimed at determining the quality control of product, the most common types defect in product, the factors in causing defect in product, the action that should be taken to prevent the defect of product at UKM Tahu Haji Mamad by using Statistical Processing Control.  this type of research is descriptive with quantitative approach. Collectingdata using interviews and observations, data analysis techniques using four tools ofquality control, the check sheet, histogram, a causal diagram, and a control chart p. Defective products in the finished product every time it is produced indicates that the quality control carried out by UKM tofu Haji Mamad is still not optimal.Observations and observations made at the Haji Mamad Tofu Factory for 10 days found many defective products which every day averaged around 46 tofu products.Theresults showed there are five types of damage to the product know, that smell, texture,hard, soft texture, there are dirt, and the wrong cut. The most dominant is the kind ofdamage a hard texture, which is about 41.74% compared to all the damage knew theothers. P control chart analysis results are known there are 6 observations that areoutside the control limit of a total of 10 observations.